Samoa : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Samoa. (IMF Staff Country Reports; Country Report, 2017)
This 2017 Article IV Consultation highlights Samoa's continued good economic performance. Economic activity picked up during 2015/16 driven by tourism arrivals, lower fuel prices, and new fish processing facilities, further boosted by two major sporting events and infrastructure projects. Although the pace will moderate in 2017/18 and in 2018/19 with the closure of a large manufacturing plant, growth is expected to remain buoyant. The outlook is moderately positive though subject to downside risks related to Samoa's vulnerability to natural disasters, elevated contingent liabilities, and withdrawal of correspondent banking relationships. Given Samoa's reliance on workers' remittances, the closure of bank accounts of money transfer operators heightens the risk of a disruption to remittance payments.